Understanding the role of Principals and the use of computers in secondary schools - Naicker, Visvanathan (South African Journal of Higher Education, 2016)
This study investigated the principals’ views of the use of computers in 32 secondary schools in Cape Town, South Africa. Principals’ of schools use computers to assist them in their administrative and managerial duties. The promotion and support from the principal regarding the use of computers in their schools, depends on how useful the principal considers computers to be. The research question of this study discusses attitudes and views of principals about the importance of computers, the Information Communication and Technology (ICT) policy, computer resources and issues related to the use of computers in schools. Qualitative analysis was used because it allowed the researcher to investigate trends or patterns of similarities. Content analysis was used to analyse the data. The researcher was searching for themes and trying to get a sense of the ‘why’ and ‘how’ principals related to the use of computers in their schools. Data was collected from the thirty-five questionnaires completed by the principals of their respective schools. The objective of this study was to investigate the role played by the principal regarding the use of computers in their schools. The study found that principals strongly believed computers must never replace the value of educators. The role model position of an educator in the classroom is critical especially to those learners who come from poor backgrounds. Principals profess that the purchasing, maintenance and support of computers are their biggest constraints.